2004
DOI: 10.1080/10810730490447084
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Tone, Message, and Broadcast Parameters in Youth Anti-smoking Advertisements

Abstract: This study supports mounting evidence that negative emotion in anti-smoking advertisements is effective with youth audiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 24 publications
14
129
3
4
Order By: Relevance
“…In our earlier section of this research we have mentioned and included sadness, anger , fear because these are the important emotional domains that influence a message to be recalled whereas funny, happy or boring ads was not. Similar conclusion was drown by Biener, Gilpin, Albers, (2004) in their research work. Respondent also agreed on frequent exposure to anti-tobacco advertising shifts attitudes and believes that subsequently lead to behavior change.…”
Section: Resultssupporting
confidence: 77%
“…In our earlier section of this research we have mentioned and included sadness, anger , fear because these are the important emotional domains that influence a message to be recalled whereas funny, happy or boring ads was not. Similar conclusion was drown by Biener, Gilpin, Albers, (2004) in their research work. Respondent also agreed on frequent exposure to anti-tobacco advertising shifts attitudes and believes that subsequently lead to behavior change.…”
Section: Resultssupporting
confidence: 77%
“…These results are consistent with fi ndings from other studies that PSAs that emphasize the short-and long-term consequences of smoking are most effective (e.g., Biener, 2002 ;Biener et al, 2004 ;cf., Goldman & Glantz, 1998 ) and that PSAs that emphasize tobacco industry manipulation are least effective ( Pechmann & Reibling, 2006 ) in affecting adolescent smoking. More important, however, the results of the present study go beyond fi ndings from previous research by showing that the effi cacy of PSAs that emphasize the long-term effects of smoking can be enhanced by using actors who are perceived by adolescents to be more appealing (i.e., more attractive and likeable).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, other studies found that antismoking advertisements that emphasize normative information are lower in perceived effectiveness compared with advertisements that emphasize the long-term consequences of smoking ( Biener, 2002 ;Biener, Ji, Gilpin, & Albers, 2004 ). Moreover, other studies found that a focus on short-term social and health consequences was more appealing to youth than a focus on long-term consequences ( Beaudoin, 2002 ).…”
Section: Original Investigationmentioning
confidence: 61%
“…The latter was the only campaign that included graphic imagery (fat poured from a soda bottle and images of heart attack and amputation). While some prior studies have focused on depiction of negative health effects as a pathway to achieving an emotional reaction or fear response (60) , we further found that a number of campaigns mentioned obesity-related diseases without achieving an overall negative valence and without use of graphic imagery. Even where they do not produce substantial negative emotional arousal, appeals related to the longterm effects of unhealthy behaviours may nevertheless be effective in some contexts (27) .…”
Section: Discussionmentioning
confidence: 80%